Radiological, geochemical, and mineralogical characterization of natural stones used in turkey - Yapici N.; Gezer F.; Nurlu N.; Turhan S.; Ufuktepe Y. (National Library of Serbia, 2017)
In the study, radiological, geochemical, and mineralogical characterization of natural stone samples used for covering or ornamental purposes collected from different quarries in Turkey was done using gamma spectrometric technique with high-purity germanium detector, X-ray fluorescence spectroscopic technique, X-ray diffraction technique and thin sections. The mean activity concentrations of 226Ra, 232Th, and 40K were measured in natural stone samples as 28.9, 30.8, and 355.0 Bqkg-1, respectively. The assessment of radiological hazards from utilization of stone samples as covering or ornamental material in building sector was made by estimating activity concentration index, absorbed gamma dose rate and annual effective dose rate. The examined natural stone samples were composed of calcite, dolomite, quartz, orthoclase, albite, biotite, hornblende, oligoclase, olivine and talc.
Keywords: geochemical characterization; Mineralogical characterization; Activity concentration; mineralogical characterization; QC770-798; annual effective dose; Annual effective dose; Radioactivity; radioactivity; Nuclear and particle physics. Atomic energy. Radioactivity; natural stone; Natural stone; activity concentration; Geochemical characterization